STRATEGI PENINGKATAN KUALITAS PRODUK AYAM GORENG RUMAH MAKAN AYAM GORENG ASLI PRAMBANAN RENON, DENPASAR - Ganantrya, Pandila Diahtaradipa; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Consumer satisfaction in a restaurant can be improved through good product quality in accordance with the wishes and needs of consumers. Improving product quality is an important problem for a restaurant because it is beneficial for restaurants and consumers. The purpose of this study are: (1) to know the attributes of fried chicken that are considered important by consumers in the original Prambanan fried chicken restaurant, (2) to measure the level of importance of the quality of fried chicken products, (3) to measure the level of consumer satisfaction with the quality of fried chicken products and (4) knowing the strategy to improve the quality of fried chicken products. This study uses the Quality Function Deployment (QFD) method. The results of this study indicate that there are 11 attributes of product quality that are considered important by consumers with very important criteria. The biggest value of consumer interest is the attribute of fried chicken taste of 3.78. On the value of consumer satisfaction attributes of fried chicken chili variants have the smallest value of 3.08 with the highest IR of 1.30 need to provide and improve the quality of the product on the attributes of the fried chicken chili sauce. Keywords : fried chicken, product quality, customer satisfaction, quality function deployment (QFD)